I’jaz Al-Qur’an dan Relevansinya dengan Perkembangan Ilmu Pengetahuan dan Teknologi - Nana Mahrani (Hikmah, 2021)
This study aims to analyze the nature of the i'jaz of the Qur'an, its significance, and its relevance to the development of science and technology. This research uses library research method, with documentation data collection techniques. The primary source in this study is the Qur'an and the secondary source is mabahits fi ulum al-Qur'an, Manahil Al-Urfan Fi-Ulum Al-Qur'an. The results of the study show that the essence of i'jaz Al-Qur'an is the science of the Qur'an which discusses the strength of the composition of the pronunciation and content of the Qur'an, so that it can beat Arabic linguists and other experts. Its significance further strengthens the originality of the Qur'an, strengthens the belief of Muslims in religion and opens the hearts of non-Muslims, explores the vast sea of ​​knowledge in the Qur'an, shows that the Qur'an is not only suitable for the time of the Prophet but relevant forever. Its relevance to science and technology is that the Qur'an is not a book of science and technology but contains scientific cues that can be used as a basis for the development of science and technology.